Safety data in randomised real-world evidence studies: Salford Lung Study learnings. Issue 2 (31st May 2021) - Harvey, Catherine; Woodcock, Ashley; Vestbo, Jørgen; Crim, Courtney; Frith, Lucy; Bakerly, Nawar Diar; New, John P.; Williams, Claire; Elkhenini, Hanaa; Majeed, Nasir; Cardwell, Glenn; Collier, Susan; et al.
Evidence to support clinical decision making must be based on safety data that have been captured, analysed and interpreted in a robust and reliable way. Randomised real-world evidence (RRWE) studies provide the opportunity to evaluate the use of medicines in patients and settings representative of routine clinical practice. However, elements that underpin the design of RRWE studies can have a significant impact upon the analysis, interpretation and implications of safety data. In this narrative review, we use data from the Salford Lung Study; two prospective, 12-month, open-label, parallel-group, phase III randomised controlled trials conducted in primary care in the UK; to highlight the importance of capturing treatment modifications when attempting to evaluate safety events according to actual treatment exposure. We demonstrate that analysing safety data by actual treatment received ( i.e. accounting for the treatment modifications that occur routinely in the primary care setting) provides additional insight beyond analysing according to randomised treatment strategy only. It is therefore proposed that understanding of safety data from RRWE trials can be optimised by analysing both by randomised group and by actual treatment received. Using results from the Salford Lung Study, this review demonstrates that the understanding of safety data from randomised real-world evidence studies can be optimised by analysing both actual treatment received and randomisation group https://bit.ly/3p7zPXU